KELUARGA SEBAGAI KOMUNITAS IMAN PERTAMA DALAM TEOLOGI PEMURIDAN KONTEKS INDONESIA - Iren; Diana Banne Arruan; Tirsa; Torsir Pasauran; Irawati Tandibua (Adisam Publisher, 2026)
This research aims to examine the role of the family as the primary faith community in discipleship theology relevant to the Indonesian context. The problem addressed is the weakening of the family's function as the primary discipleship agent, due to parents' tendency to delegate spiritual responsibilities to the church and school. The method used is descriptive qualitative research with a library study approach, through the study of biblical texts and theological-educational literature. The results show that the family is a divine institution that precedes the church and school as a space for discipleship, as mandated in Deuteronomy 6:6-7. In the Indonesian context faced with the pressures of modernization, urbanization, and value shifts, Christian families need to be re-empowered as centers of discipleship through integrative spiritual habituation and strategic collaboration between family and church. This research affirms that effective discipleship does not begin from institutions, but from intimate relationships in households living in God's word.